Analisis Pemberdayaan Kelompok Masyarakat Melalui Usaha Kerajinan Tangan Berbasis Ekonomi Kreatif Oleh Yayasan Dreamdelion (Studi Kasus Di Rusun Pinus Elok Jakarta Timur) - Nindita Arrum Wardani; Dewi Nurbaiti (JAMBIS : Jurnal Administrasi Bisnis, 2021)
The poverty in Indonesia is a thing that most of us have known about. This condition also needs government and people to contribute so they could support any business for increasing public welfare. This day, creative economy business has predicted as the future industry. Beside of the economy, creative economy also relates with culture and people dimension. The benefit of creative economy includes working opportunity for fashion and any sector that has big chances empowering employees from society with any levels of skill itself. People’s economic growth could not be separated with Non Government Organization’s (NGO’s) contribution which is doing some training skill and empowering a community people with the aim of improving their welfare. The NGO who is doing the empowerment based of creative economy is Dreamdelion Foundation with handicrafts as results. Research question of this essay consist of what kind of obstacles and empowerment programme that Dreamdelion Foundation does for people. What kind of business and the impact of income improvement for people who join the empowerment programme. Qualitative research methods is the research which is applying interaction between the writer towards the inspected facts. The research’s results are the most difficult obstacle is changing people’s paradigm, empowerment programme that has been performed is sewing, kind of business that has applied are producing bags and also the other souvenirs, average income is between Rp 850.000-1.500.000.